2019
DOI: 10.3390/rs11212563
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Photosynthesis Solely from Solar-Induced Chlorophyll Fluorescence: A Global, Fine-Resolution Dataset of Gross Primary Production Derived from OCO-2

Abstract: Accurately quantifying gross primary production (GPP) globally is critical for assessing plant productivity, carbon balance, and carbon-climate feedbacks, while current GPP estimates exhibit substantial uncertainty. Solar-induced chlorophyll fluorescence (SIF) observed by the Orbiting Carbon Observatory-2 (OCO-2) has offered unprecedented opportunities for monitoring land photosynthesis, while its sparse coverage remains a bottleneck for mapping finer-resolution GPP globally. Here, we used the global, OCO-2-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(152 citation statements)
references
References 60 publications
4
145
3
Order By: Relevance
“…Appling these two C 3 and C 4 models, the RMSEs of estimated GPP at the daily, monthly, and yearly scales are 1.81, 1.33, and 0.89 gC/m 2 /d, respectively (Figures 3d and 4). The estimation accuracies in GPP are generally higher than previous studies, such as RMSE of 1.90 and 1.21 gC/m 2 /d at monthly and yearly scale in Li and Xiao (2019).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Appling these two C 3 and C 4 models, the RMSEs of estimated GPP at the daily, monthly, and yearly scales are 1.81, 1.33, and 0.89 gC/m 2 /d, respectively (Figures 3d and 4). The estimation accuracies in GPP are generally higher than previous studies, such as RMSE of 1.90 and 1.21 gC/m 2 /d at monthly and yearly scale in Li and Xiao (2019).…”
Section: Discussioncontrasting
confidence: 63%
“…Owing to the physiological link between SIF and GPP, a growing number of studies have attempted to estimate GPP from satellite SIF using empirical SIF‐GPP relationships (Frankenberg et al, 2011; Li & Xiao, 2019; Zhang, Guanter et al, 2018). These empirical relationships are generally calibrated with clear‐sky GPP and SIF, which could cause uncertainties in GPP estimation under cloudy sky conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as those of Zhang et al [184], Li et al [176], and Yu et al [185] demonstrated a way to improve the resolution of OCO-2 and extend the OCO-2 SIF products back to 2000. These improved SIF products have a higher resolution (0.05 • ), longer data record (from 2000 to present), and are globally contiguous; they will have more flexible and wide applications such as estimating higher-resolution GPP at local, regional, and global levels compared to the original ones [186].…”
Section: Limitations Of Spaceborne Top-of-canopy Sif Observationsmentioning
confidence: 99%
“…We re-sampled it to 1 km pixel size before being extracted based on site locations. The GOSIF GPP product was developed by Li and Xiao [24], with a 0.05 • spatial resolution and an eight-day time step for the period from 2000 to 2018. The GOSIF GPP product benefited from the breakthrough of two key matters, the relationship between SIF and GPP, and SIF data with high spatial and temporal resolutions.…”
Section: Remote Sensing Products and Processingmentioning
confidence: 99%
“…Therefore, the land cover maps were not taken into account when the GOSIF products are produced. Similarly, Li and Xiao [24] used a nearly universal rather than biome-specific SIF-GPP relationship to get the GOSIF GPP product. In a nutshell, the GOSIF GPP reduced the impact of land cover classification uncertainty to some extent.…”
Section: Error Sources Of Remotely-derived Productsmentioning
confidence: 99%